Soil analysis and survey data for selected farms in western Kenya under annual and perennial cropping system - Korir, Mercy Jebet; Nyawira, Sylvia Sarah; Notenbaert, An Maria Omer (2025)
The data includes survey and soil data collected in western Kenya under annual and forage crop systems. The objective of this study was to compare soil organic carbon stocks under the two cropping systems and to compare the potential of forages to sequester carbon.The data includes survey and soil data collected in western Kenya under annual and forage crop systems. The objective of this study was to compare soil organic carbon stocks under the two cropping systems and to compare the potential of forages to sequester carbon.